다이어트경험이 있는 여대생의 우울과 자기낙담간 관계에서 폭식행동의 매개효과 - 박지선(Jisun Park) (Seuteureseu yeon-gu (Online), 2019)
본 연구는 다이어트 경험이 있는 여대생의 우울과 자기낙담 간 관계에서 폭식행동의 매개 효과를 알아보기 위해 수행되었다. 이를 위해 299명의 여대생을 대상으로 다이어트 경험 유무, 우울, 폭식 행동, 자기낙담에 관한 설문을 실시한 후, 최종적으로 296명의 자료를 분석하였다. 그 결과, 첫째, 296명 중 76%의여대생이 다이어트 경험이 있는 것으로 보고하여 다이어트 경험이 없는 여대생보다 훨씬 더 많았다. 둘째, 다이어트 경험이 있는 여대생의 경우 우울, 폭식 행동 및 자기낙담 간 상관이 모두 유의하였다. 셋째, 다이어트 경험이 있는 여대생의 우울과 자기낙담 간 관계에서 폭식행동이 부분 매개 효과를 보였다. 이를 토대로 대학생의 자기낙담에 개입 방안을 제안하고 본 연구의 의의와 제한점을 논하였다. Background: This study has been carried out in order to investigate the mediating effect of depression on the relationship of self discouragement and binge eating behaviour of university female students with diet experience. Methods: The data of diet experience existence, depression, binge eating behavior and self discouragement were obtained. Lastly, the total data of 296 undergraduate female students were analyzed. Results: The results of this study were as follows. First, 76% of college women reported a Diet experience. This figure was more than three times the female students reported that this diet experience. Second, In college students with diet experience, the variables of depression, binge eating behavior and self-disappointment were all significantly correlated. Third, binge eating behavior partially mediated the relation between depression and self discouragement. Conclusions: Binge eating behavior mediated the relation between depression and self discouragement of University female students with diet experience. KCI Citation Count: 1